Mediating effect of emotional intelligence on influence of transformational leadership on secondary school teachers' organisational commitment in Terengganu - Farah Wahida Jaafar
Teachers' organisational commitment is crucial to the school organisation in achieving the schools'vision. There exists an issue of teachers' commitment among Malaysian school teachers due to improper leadership styles practised by the school principals. Proactive actions need to be taken to ensure teachers' level of commitment can be further improved in accordance with current needs and situations. In the educational context of producing excellent schools, the principals need to be aware of their roles in influencing teachers' commitment. An effective leadership style employed by the principals will create a harmonious relationship and strong co-operation which can affect teachers' commitment. Previous researches have proven that transformational leadership is the most suitable style to enhance the level of teachers' organisational commitment in facing the changes and challenges in the education system. Emotional intelligence is the main factor affecting the transformational principals and consequently shows a positive effect towards teachers' organisational commitment. This research is a survey of the direct and indirect effects of transformational leadership style towards teachers' organisational commitment with emotional intelligence as a mediator. A sample size of 150 secondary school teachers was drawn through simple random sampling from a population of 8011 national secondary school teachers in Terengganu. The data were collected through administering close-ended structured questionnaires. Structural Equation Modeling (SEM) was used to analyse the effects of the exogeneous construct (transformational leadership style) on the endogenous construct (teachers' organisational commitment) and the role of emotional intelligence as a mediator. The findings revealed that the exogeneous construct (transformational leadership style) has a significant direct and indirect effects towards the endogenous construct (teachers' organisational commit: cnt . The regression weight for the direct effect is 0.464 (p-value < 0.05) which means that there was a significant effect of transformational leadership style towards teachers' organisational commitment. The regression weight for indirect effect is 0.122 (p-value < 0.05) which means emotional intelligence was a mediator. The probability of bootstrap for direct effect is 0.004 and for indirect effect is 0.013 which means both effects were significant (p-value < 0.05). It can be concluded that emotional intelligence show a partial mediation on t &1sformational leadership style towards teachers' organisational commitment. The fi dings have clearly achieved the objectives and supported the hypotheses of the research. Emotional intellig nee plays a crucial role in transformational principals in leading their school organisations towards success. Emotionally intelligent principals tend to enhance the level of teachers' organisational commitment. Committed teachers produce excellent students with quality potentials that will benefit the country's development.